Variation in the capture of Neoleucinodes elegantalis Guenée (Lepidoptera: Crambidae) males using commercial sex pheromones on three solanaceous hosts (2017)
ABSTRACT: Neoleucinodes elegantalis Guenée (Lepidoptera: Crambidae) represents the most damaging pest of the Solanaceae family. Current studies have demonstrated that the species has differentiated into four races according to variations in female genitalia, wing morphometrics and sequencing of the Cytochrome Oxydase 1 (CO1) mitochondrial gene. The number of males captured in Colombia and Ecuador were registered using traps baited with two sex pheromone: Neolegantol® and P228. These pheromones were synthesized using natural female pheromones collected in Solanum lycopersicum L. plantations in Venezuela. In Colombia, the number of male catches was significantly higher for Neolegantol® than for P228 and this number was significantly higher on S. lycopersicum followed by S. quitoense and S. betaceum. The haplotype net obtained with the CO1 gene produced two main clusters: one cluster was comprised by specimens from S. lycopersicum and S. quitoense plants (both with medium sized female genitalia) and the other cluster by specimens from S. betaceum (large sized genitalia). The Neolegantol® pheromone was also tested in Ecuador, however, insignificant number of males were attracted. Results suggest that pheromone composition or concentration, host biotypes and geographic location are relevant to monitor populations of N. elegantalis. Further studies of the species should concentrate on establishing the pheromone composition and concentration among the four biotypes.